Exploring The Perception and Potential of Bullying among First-Year Medical Students In Indonesia: A Qualitative Study - Saleh, Rizki Fitrah Rahmani; Sopardireza, Azriel Fasha; Wijaya, Akbar Rahmad; Maharani, Berlian Nur; Sari, Sylvia Mustika (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: The quality of medical education in Indonesia is vital for achieving the Sustainable Development Goals (SDGs). However, bullying in medical education remains a global concern, including in Indonesia. The hierarchical structure in Indonesian medical schools often places first-year students in subordinate roles, increasing their vulnerability to bullying. This highlights the need to explore perceptions of bullying among first-year medical students.Aims: To explore first-year medical students' perceptions of bullying, including its definition, potential occurrence, attitudes, and future plans related to bullying in Indonesian medical education.Method: This qualitative study employed a phenomenological approach. Respondents were recruited through the Indonesian medical student organization to ensure representation from across Indonesia. Forty-eight respondents from 16 institutions participated. Data were collected through online focus group discussions (FGDs) and analyzed using coding, categorization, and thematic analysis. Trustworthiness was ensured through member checking and multiple coders. Results: Five themes emerged: 1) Bullying was defined as intimidating behavior occurring within power gaps; 2) Verbal, physical, and cyber-bullying were identified as potential forms; 3) Bullying commonly arises from physical, social, and academic gaps; 4) Bullying negatively impacts mental health, social well-being, and academic performance; and 5) Support systems, reporting mechanisms, and anti-bullying services are essential.Conclusion: Bullying is prevalent among first-year medical students in Indonesia, affecting well-being, academics, and professional growth. Hierarchical culture and peer pressure are key contributors. Comprehensive policies and educational strategies are crucial for fostering a safer, inclusive academic environment, improving medical education outcomes, and supporting the SDGs.